2020
DOI: 10.1007/s10529-020-02852-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of msFGFR2c on the epithelial-to-mesenchymal transition of AE2 cells in pulmonary fibrosis

Abstract: In interstitial fibrosis, alveolar epithelial type II (AE2) cells fail to repair damaged epithelium. However, whether this dysfunction is related to fibroblast growth factor (FGF) signal pathway and how it affects the fibrotic process remains unclear. In our study, the medium of the human foetal lung fibroblast cell line MRC-5 (Med) can induce epithelial-to-mesenchymal transition (EMT) in AE2 cells, we also found that TGF-b in Med can induce FGF-2 and CTGF expression in AE2 cells. TGF-b or CTGF exposure trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In addition, the expression levels of FGF2, α-SMA, and collagen have been shown to be significantly increased in renal interstitial fibrosis tissues, suggesting that FGF2 may eventually cause renal interstitial fibrosis by promoting cellular EMT, which is consistent with the current study (Du et al, 2015;Jieming et al, 2020;Kurimoto et al, 2017;Lee et al, 2019;Li et al, 2017;Masola et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the expression levels of FGF2, α-SMA, and collagen have been shown to be significantly increased in renal interstitial fibrosis tissues, suggesting that FGF2 may eventually cause renal interstitial fibrosis by promoting cellular EMT, which is consistent with the current study (Du et al, 2015;Jieming et al, 2020;Kurimoto et al, 2017;Lee et al, 2019;Li et al, 2017;Masola et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Fibroblast growth factor 2 (FGF-2) is a member of the mammalian fibroblast growth factor family, which consists of at least 23 members (22 identified in humans to date) (Bikfalvi et al, 1997;Yun et al, 2010). At present, many studies have shown that FGF2 plays an important role in the process of EMT in renal fibrosis (Du et al, 2015;Li et al, 2017;Masola et al, 2012) and other organ fibrosis (Jieming et al, 2020;Kurimoto et al 2017;Lee et al, 2019); however, the precise mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effects of the FGFR2 variants on hepatic fibrosis are lacking. In the lung, a mutant of soluble FGFR2C extracellular domain improved fibrotic remodelling suggesting a profibrotic role of FGFR2C signalling, and the shift from FGFR2B to FGFR2C expression in alveolar epithelial cells was suggested to be important for pulmonary fibrosis 136 . Whether this shift also plays a role in hepatic fibrosis remains to be elucidated.…”
Section: Role Of Fgf‐receptors In Hepatic Fibrosismentioning
confidence: 99%
“…ELISA assay: Refer to Wang's method and follow the manufacturer's instructions to carry out the test [19]. ELISA kit (Quantikine ™ ; R&D Systems, Minneapolis, MN, USA) and 96-well plates (Corning, New York, NY, USA).…”
Section: Cell Lines Reagents and Antibodiesmentioning
confidence: 99%